Alterations of Electrophysiological Properties and Ion Channel Expression in Prefrontal Cortex of a Mouse Model of Schizophrenia - Mi, Zhen; Yang, Jun; He, Quansheng; Zhang, Xiaowen; Xiao, Yujie; Shu, Yousheng (Frontiers in Cellular Neuroscience, 2019)
Maternal immune activation (MIA) and juvenile social isolation (SI) are two most prevalent and widely accepted environmental insults that could increase the propensity of psychiatric illnesses. Using a two-hit model, we examined the impact of these two factors on animal behaviors, neuronal excitability and expressions of voltage-gated sodium (Nav) and small conductance calcium-activated potassium (SK) channels in the prefrontal cortex (PFC). We found that combining MIA with SI exacerbates a number of schizophrenia-related behaviors. Patch clamp recordings revealed alterations in electrophysiological properties of PFC layer-5 pyramidal cells, including hyperpolarized resting membrane potential, increased input resistance and enhanced medium after-hyperpolarization (mAHP). MIA-SI increased the ratio of the maximal slope of somatodendritic potential to the peak slope of action potential upstroke, indicating a change in perisomatic Nav availability. Consistently, MIA-SI also significantly increased the expression level of Nav1.2 and SK3 channels that contribute to the somatodendritic potential and the mAHP, respectively. Together, these changes may alter neuronal signaling in the PFC and behavioral states, representing a molecular imprint of environmental insults associated with neuropsychiatric illnesses.